ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK PADA MATERI PERPANGKATAN DAN BENTUK AKAR - Refandi, Ricky (Jurnal Edukasi dan Penelitian Matematika, 2023)
This study examines the multiplication and root form problem solving skills of grade IX junior high school students. This qualitative research was descriptive in nature. Research involves planning, conducting and analyzing. The research subjects were three children who had the highest, average, and lowest mathematics scores in their class, using the KKM score as the assessment reference. They used the Math Problem Solving Ability Test. The Grade IX SMP students were unable to understand the problem, plan the solution, solve problems according to plan, or check the multiplication and root form material, so they had low mathematical problem-solving ability in these areas.Keywords: Analysis of Students Mathematical Ability, Mathematical Problem Solving Ability, Exponentials and Roots Material